1990
DOI: 10.1161/01.hyp.15.3.274
|View full text |Cite
|
Sign up to set email alerts
|

Tonic cardiovascular effects of angiotensin II in the ventrolateral medulla.

Abstract: The rostral and caudal parts of the ventrolateral medulla play a major role in the control of blood pressure. Both regions contain a high density of receptor binding sites for angiotensin II, and it has been shown previously that microinjection of angiotensin II into the rostral ventrolateral medulla causes a rise in blood pressure. The aims of this study were to determine the cardiovascular effects of microinjection of angiotensin II and its specific antagonist T here is considerable evidence that angiotensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
90
3
3

Year Published

1991
1991
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(104 citation statements)
references
References 33 publications
8
90
3
3
Order By: Relevance
“…However, we did not observe any change in blood pressure or RSNA by giving an effective dose of Sarile (10 pmol) to urethane-anesthetized rabbits. This contrasts the findings of other groups that found a marked reduction in blood pressure with this agent or with [Sar 1 ,Thr 8 ]-Ang II (41,45). A recent study suggests, however, that this effect is not related to the blockade of Ang II receptors (46).…”
Section: Cardiovascular Effects Of Blocking Endogenous Ang II In the contrasting
confidence: 95%
See 1 more Smart Citation
“…However, we did not observe any change in blood pressure or RSNA by giving an effective dose of Sarile (10 pmol) to urethane-anesthetized rabbits. This contrasts the findings of other groups that found a marked reduction in blood pressure with this agent or with [Sar 1 ,Thr 8 ]-Ang II (41,45). A recent study suggests, however, that this effect is not related to the blockade of Ang II receptors (46).…”
Section: Cardiovascular Effects Of Blocking Endogenous Ang II In the contrasting
confidence: 95%
“…Andreatta and colleagues (40) suggested that the RVLM may contain a reninangiotensin system since Ang I applied to the ventral surface of the brainstem of the cat produced an increase in blood pressure after conversion to Ang II. Sasaki and Dampney (41) found that the sites which produced the greatest increase in blood pressure in the RVLM were also the sites containing the highest concentration of Ang receptors. We initially mapped various dorsal and ventral sites with microinjections of Ang II and found that marked pressor responses were observed only when Ang II was administered into a discrete region of the RVLM corresponding to the subretrofacial nucleus.…”
Section: Actions Of Ang II In the Rostral Ventrolateral Medulla On Bamentioning
confidence: 98%
“…Muratani et al 26 and Alzamora et al 27 obtained similar results. As the baro-excited CVLM neurons formed synapses with the RVLM neurons, these previous results [25][26][27] support our present data. However, the findings of their studies and ours do not answer the question as to whether Ang-II activates the baro-excited CVLM neurons directly.…”
Section: Baro-excited Cvlm Neuronssupporting
confidence: 92%
“…However, the findings of their studies and ours do not answer the question as to whether Ang-II activates the baro-excited CVLM neurons directly. Considering the results of previous studies, [25][26][27] we cannot deny the possibility that Ang-II may have activated non-baroexcited CVLM neurons and that these neurons in turn sent synaptic activity to the baro-excited CVLM neurons.…”
Section: Baro-excited Cvlm Neuronsmentioning
confidence: 72%
See 1 more Smart Citation